(untitled) (The Strategic Review for Southern Africa, 2020)
In this article, the author uses Afrocentricity in order to provide an African point of view in respect of the analysis of the United States (US) foreign policy towards Africa. Given the dominance of mainstream thinking about the US foreign policy that takes for granted US as a prominent and primary in defining the relations, this article employs historical sensibility in order to trace the US relationship with Ghana and Tanzania using Afrocentric lens. This discourse is often partially understood due to the lack of an Afrocentric perspective on the existing literature in this aspect of Strategic Studies. History is crucial in this regard because the past provides a sound basis for understanding the present and future. This helps challenge the thinking overly informed by mainstream theories in Strategic Studies. As it shall be seen below, such a paradigm remains critical in highlighting the peculiarity of the US relationship with Ghana and Tanzania and in providing a deeper understanding of underlying dynamics in US foreign policy towards Africa. To realise the purpose of this article, the author relies methodologically on interdisciplinary critical discourse and conversations in their widest forms.